2018
DOI: 10.1186/s13054-018-2250-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mechanically ventilated patients treated in ICU and non-ICU settings in Japan: a retrospective database study

Abstract: BackgroundIn most countries, patients receiving mechanical ventilation (MV) are treated in intensive care units (ICUs). However, in some countries, including Japan, many patients on MV are not treated in ICUs. There are insufficient epidemiological data on these patients. Here, we sought to describe the epidemiology of patients on MV in Japan by comparing and contrasting patients on MV treated in ICUs and in non-ICU settings. A preliminary comparison of patient outcomes between ICU and non-ICU patients was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 11 publications
2
55
2
1
Order By: Relevance
“…Previously, we showed that 46.4% of these patients (including those with noninvasive MV) are treated in non-ICU settings in Japan (2). The mortality rate of these patients was higher than in those treated in ICU settings.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, we showed that 46.4% of these patients (including those with noninvasive MV) are treated in non-ICU settings in Japan (2). The mortality rate of these patients was higher than in those treated in ICU settings.…”
Section: Introductionmentioning
confidence: 94%
“… 16 Iwashita et al clarified the differences in the duration of the use of a mechanical ventilator, mortality rate, and intensive care treatment implementation status depending on admission to an intensive care unit. 17 Kuwabara et al investigated the relationship between the use of albumin and catecholamines for subarachnoid hemorrhage and in-hospital mortality, consciousness deterioration at discharge, and reintubation rate. 18 Kido et al conducted a comparative study on the differences in in-hospital mortality in patients with acute lung injury and acute respiratory distress syndrome based on the administration of sivelestat.…”
Section: Dpc-related Studiesmentioning
confidence: 99%
“…The square waveform or decelerating inspiratory flow for the inspiratory flow-time profile are commonly used. For volume targeted ventilation, apart from FiO 2 , PEEP, trigger mode and sensitivity, 1 V T 2 ; inspiratory waveform 3 ; mandatory respiratory rate [f] 4 ; and timing such as inspiratory/expirium ratio or inspiratory time/total breathing time and inspiratory time (T i ) is set 29 …”
Section: Mechanical Ventilation Modesmentioning
confidence: 99%
“…A one-quarter of these patients remain in the ED for more than 5 hours, and their mortality is significantly higher than the other patients admitted to the ICU 2 . In Japan, it is reported that 46.4% of patients 3 requiring MV are monitored in non-ICU settings. EDs is one of these places that frequently monitor mechanically ventilated patients.…”
Section: Introductionmentioning
confidence: 99%